2020
DOI: 10.1590/0037-8682-0024-2020
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis notifications among pregnant women in Campo Grande, state of Mato Grosso do Sul, Brazil, 2011 to 2017

Abstract: Introduction: Syphilis is a sexually transmitted infection caused by Treponema pallidum. Considering the high rates of syphilis in pregnancy and congenital syphilis reported in Brazil in the past, and their serious consequences, this study described the epidemiological and clinical profile of pregnant women with a confirmed diagnosis of syphilis in Campo Grande, in the state of Mato Grosso do Sul, Brazil, from 2011 to 2017. Methods: This is a descriptive study, based on syphilis notifications among pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
0
0
2
Order By: Relevance
“…In this study, sociodemographic variables (age group, education, and skin color) were not statistically associated with the occurrence of CS. Even so, the predominant age group was similar to that found in other Brazilian studies; [13][14][15] this may reflect vulnerability related to "age and emotional immaturity" (especially with 20-24 years old), influence of social groups, early onset of sexual life, and not using condoms during sexual intercourse. 16 As for education, the lack of association with the outcome may be a consequence of the number of forms without information (or with ignored information), as well as the sample size.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, sociodemographic variables (age group, education, and skin color) were not statistically associated with the occurrence of CS. Even so, the predominant age group was similar to that found in other Brazilian studies; [13][14][15] this may reflect vulnerability related to "age and emotional immaturity" (especially with 20-24 years old), influence of social groups, early onset of sexual life, and not using condoms during sexual intercourse. 16 As for education, the lack of association with the outcome may be a consequence of the number of forms without information (or with ignored information), as well as the sample size.…”
Section: Discussionsupporting
confidence: 79%
“…19,23,24 In the present study, 38.8% of the notification forms had the clinical classification field "no information or ignored" (data not shown). This lack of information on the clinical classification was also evidenced in the literature, 13,19,21,22 showing the importance of adequate classification and correct completion of the notification forms, thus contributing not only to the treatment definition but also to research and follow-up of reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este último ponto ressalta a importância dos métodos educacionais e campanhas de esclarecimento à população geral acerca da prevenção da contaminação e infecção. Muito embora se acreditava que tais métodos preventivos sejam bem conhecidos, a falha na aplicabilidade e o aumento de casos de sífilis em gestante alertam para possíveis falhas nesta etapa 15,18,19 .…”
Section: Discussionunclassified
“…A sífilis gestacional afeta cerca de 1,5 milhão de gestantes por ano em todo o mundo 4,10 . No Brasil, segundo os dados fornecidos pelo Boletim Epidemiológico da Sífilis (2020), em 2019, houve 61.127 casos de sífilis em gestantes (taxa de detecção de 20,8/1.000 nascidos vivos), 24.130 casos de sífilis congênita (taxa de incidência de 8,2/1.000 nascidos vivos) e 173 óbitos por sífilis congênita (taxa de mortalidade de 5,9/100.000 nascidos vivos) 6 . Ademais, conforme os Indicadores de Sífilis do Departamento Doenças de…”
Section: Introductionunclassified